PERTANGGUNGJAWABAN PIDANA ANGGOTA KEPOLISIAN DALAM HAL PENEMBAKAN DENGAN UNSUR KETIDAKSENGAJAAN YANG BERAKIBAT MENINGGALNYA KORBAN - Kartini Syukur; Adi Nur Rohman (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2025)
As a state governed by law, as stipulated in Article 1 paragraph (3) of the 1945 Constitution of Indonesia, the country has a legal system that regulates various aspects of national and state life, including maintaining public order. The Indonesian National Police has the duty to uphold the law, including handling criminal acts involving firearms. The use of firearms (SENPI) by the police is regulated by laws such as the Indonesian National Police Regulation No. 1 of 2009, which governs the use of force in police operations. Although firearms are intended to maintain order, misuse or negligence in their use can have fatal consequences, resulting in the victim's death. This study aims to examine the criminal liability of perpetrators of shootings caused by negligence leading to the victim's death, as well as the relevance of restorative justice in determining compensation or restitution for the victim's family. The research approach is juridical-normative with a case study, analyzing relevant legal regulations and court decisions. The study utilizes primary, secondary, and tertiary legal sources to gain a comprehensive understanding of the application of the law in cases of negligence resulting in death. Through a descriptive qualitative approach, this research is expected to provide an understanding of appropriate criminal liability and justice that can be accepted by the victim's family.